The Frequency of Lysosomal Acid Lipase Deficiency in Children With Unexplained Liver Disease - Kuloglu, Zarife; Kansu, Aydan; Selbuz, Suna; Kalayci, Ayhan G.; Sahin, Gulseren; Kirsaclioglu, Ceyda Tuna; Balci Sezer, Oya (Lippincott Williams & Wilkins, 2019)
Objectives: Evidence suggests that lysosomal acid lipase deficiency (LAL-D) is often underdiagnosed because symptoms may be nonspecific. We aimed to investigate the prevalence of LAL-D in children with unexplained liver disease and to identify demographic and clinical features with a prospective, multicenter, cross-sectional study. Methods: Patients (aged 3 months-18 years) who had unexplained transaminase elevation, unexplained hepatomegaly or hepatosplenomegaly, obesity-unrelated liver steatosis, biopsy-proven cryptogenic fibrosis and cirrhosis, or liver transplantation for cryptogenic cirrhosis were enrolled. A Web-based electronic data collection system was used. LAL activity (nmol/punch/h) was measured using the dried blood spot method and classified as LAL-D(<0.02), intermediate (0.02-0.37) or normal (>0.37). Asecond dried blood spot sample was obtained from patients with intermediate LAL activity for confirmation of the result. Results: A total of 810 children (median age 5.6 years) from 795 families were enrolled. The reasons for enrollment were unexplained transaminase elevation (62%), unexplained organomegaly (45%), obesity-unrelated liver steatosis (26%), cryptogenic fibrosis and cirrhosis (6%), and liver transplantation for cryptogenic cirrhosis (<1%). LAL activity was normal in 634 (78%) and intermediate in 174 (21%) patients. LAL-D was identified in 2 siblings aged 15 and 6 years born to unrelated parents. Dyslipidemia, liver steatosis, and mild increase in aminotransferases were common features in these patients. Moreover, the 15-year-old patient showed growth failure and microvesicular steatosis, portal inflammation, and bridging fibrosis in the liver biopsy. Based on 795 families, 2 siblings in the same family were identified as LAL-D cases, making the prevalence of LAL-D in this study population, 0.1% (0.125%-0.606%). In the repeated measurement (76/174), LAL activity remained at the intermediate level in 38 patients. Conclusions: Overall, the frequency of LAL-D patients in this study (0.1%) suggests that LAL-D seems to be rare even in the selected high-risk population.
Keywords: children; liver; lysosomal acid lipase deficiency